2019
DOI: 10.1111/vcp.12809
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphopenia and neutropenia in a dog with large granular lymphocytic leukemia

Abstract: T‐cell large granular lymphocytic leukemia (T‐cell LGLL) is the most common presentation of chronic lymphocytic leukemia (CLL) in dogs. Aleukemic or subleukemic leukemia is a particularly rare variation in both humans and dogs, where bone marrow proliferation is either not or only sparsely translated in the peripheral blood. Neutropenia is a prominent feature in cases of human T‐cell LGLL but is normally absent in canine CLL. This report describes a case of a dog presented with an almost 3‐year history of asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…Review of previously reported cases reveals a mean age of 9 years (range 4-14) across 41 cases. 5,14,[16][17][18][19][20][21][22][23] Across these previous publications, a male to female ratio of 0.7:1 was identified in contrast to the current study where male dominance was identified.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Review of previously reported cases reveals a mean age of 9 years (range 4-14) across 41 cases. 5,14,[16][17][18][19][20][21][22][23] Across these previous publications, a male to female ratio of 0.7:1 was identified in contrast to the current study where male dominance was identified.…”
Section: Discussioncontrasting
confidence: 69%
“…Across the previous canine case reports, anaemia was identified in 56% of cases, neutrophilia in 49% of cases, thrombocytopaenia in 25% of cases and neutropenia in 17% of cases (some cases exhibited more than one cytopaenia). 5,14,[16][17][18][19][20][21][22][23] In comparison with the current study, these previously reported cases exhibited anaemia at nearly three times the occurrence and thrombocytopaenia at nearly two times the occurrence, while the incidence of neutrophilia was similar.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation